Hydroacoustic activity of the ship propeller operation - Szantyr, J. A.; Koronowicz, T. (Archives of Acoustics, 2006)
The paper presents ship propellers as the source of a variable pressure field in water. The frequency spectrum of this field covers the entire audible range and beyond this range. This pressure field is generated by several physical mechanisms: the rotating hydrodynamic loading of the blades, the displacement effect of the rotating blades, the boundary layer effect, and, first of all, various forms of cavitation. The relative importance of these mechanisms is analysed and the methods of the theoretical prediction of the propeller generated variable pressure field are briefly presented. The results of the prediction are compared with experimental data.